Effectiveness of Problem Based Learning Model Assisted with Circulation System Display Media to Improve Cognitive Ability and Expressing Opinion Activities of High School Students (Journal of Biology Education, 2023)
The purpose of this study was to analyze the effectiveness of the problem-based learning model assisted by the circulation system visual aid to improve cognitive abilities and the activity of expressing high school students' opinions. This research is an experimental study with a quasi-experimental design with a two group pretest-posttest type with control group design. The population of this study were all students of class XI MIPA SMA N 1 Purwodadi which consisted of 7 classes. The samples of this research were students of class XI MIPA 2 and XI MIPA 3. Sampling was done using simple random sampling technique. The research data is in the form of cognitive ability test results and the results of observation of students' opinions expressed activities. Methods of data collection using tests (multiple choice questions pretest and posttest ) and observation sheets. The results showed that the cognitive abilities of students in the experimental class had increased based on the N-gain calculation, which was 0.53 which was in the medium category. The activity of expressing students' opinions has also increased. The percentage of activeness in expressing opinions was initially only 2.78%, increasing to 100%. The conclusion of this study is that the PBL model assisted by the circulation system visual media is effective for improving students' cognitive abilities and activities to express opinions.